Government Debt, Government Spending, and Private Sector Behavior: Reply and Update - Kormendi, Roger C.; Meguire, Philip (American Economic Review, 1990)
The preceding articles by Martin Feldstein and Douglas Elmendorf and by Franco Modigliani and Arlhe Sterling give us a welcome opportunity to return to the effects of fiscal policy on private consumption. At stake in this debate, we believe, is a potential paradigm change-from what Kormendi (1983) termed the Standard Approach, which bases private consumption on disposable personal income, to what he termed the Consolidated Approach, which bases consumption on aggregate income, government spending, and transfer payments, each with separate effects. The Standard Approach excludes Ricardian equivalence a priori. The Consolidated Approach not only incorporates Ricardian equivalence but, in its augmented form, allows one to nest the various hypotheses associated with the two approaches. Feldstein and Elmendorf argue that Kormendi's (1983) results (and implicitly those of Kormendi and Meguire, 1986), which reject the Standard Approach in favor of the Consolidated/Ricardian alternative, are not robust to the exclusion of data from World War II and other specification changes. Modigliani and Sterling argue that accounting for temporary taxes reverses our rebuttal of their 1986 comment. We first take up the challenge of Feldstein and Elmendorf before turning to Modigliani and Sterling. We then assess the validity of our preference for estimating in differences, by testing whether consumption, income, and the fiscal variables are cointegrated. Finally, we summarize what can be learned from the debate. I. Feldstein and Elmendorf